Blockchain technology to enhance information sharing in a port community : Case Vuosaari Harbour, Port of Helsinki - Tähtinen, Eero (My University, 2019)
Stakeholders operating in a port arguably form a port community, regardless of any efforts towards it. Port community system, in turn, has been extensively studied since its inception in the 1980s. Essentially, it is a shared information system between at least two port stakeholders. The recent development of more modifiable blockchain applications could contribute to existing port community systems. The theory on the adoption of novel technologies was applied in order to evaluate the current developmental stage of blockchain technology. Thus, this thesis aims at evaluating the potential of increased information sharing within a port community through means of blockchain technology. The underlying context of cargo port environment and organizational knowledge management capabilities provide the broader setting. A multiple-case study was conducted to gather empirical data from a specific port community in Vuosaari, Finland. Vuosaari Harbour is a port in Helsinki area, primarily for handling unitized cargo. Moreover, it is a traditional landlord port with private operators. Multiple semi-structured interviews were conducted among the stakeholders, including the port landlord, shipping companies, stevedores, a freight forwarder, and a public transport agency. The results are presented in accordance with selected classical methods concerning qualitative research practices, including data displays and eventual discussion based on them. The results indicate that blockchain still is a technology in its infancy. Lack of standardization and benchmarks render gaining the critical mass for any widespread port community blockchain implementation unfeasible. Moreover, the sunk costs of current information systems negatively impact the willingness to venture new information sharing models. Most potential is seen in blockchain applications that contribute to the broader supply chain, such as bill of lading as a smart contract, while the benefits for a single port community remain hidden. In the same vein, the general level of blockchain knowledge among the stakeholders was found to be rather low. Future research may yield different results, though, due to advancing knowledge and adaptation of blockchain. However, any innovation could ultimately face rejection as well.
Keywords: blockchain, cargo port, port community, stakeholder, port community system, information sharing, port landlord